"Heartstart Scotland"–initial experience of a national scheme for out of hospital defibrillation. Issue 6791 (22nd June 1991) - Cobbe, S M; Redmond, M J; Watson, J M; Hollingworth, J; Carrington, D J
Abstract : OBJECTIVE–To determine the outcome of out of hospital defibrillation in Scotland during the year after the introduction of automated external defibrillators in October 1988. DESIGN–Retrospective analysis of ambulance service reports and hospital records. SETTING–Scottish Ambulance Service and acute receiving hospitals throughout Scotland. MAIN OUTCOME MEASURES–Delay from cardiac arrest to first defibrillator shock; vital state on arrival at hospital accident and emergency department; survival to hospital discharge. RESULTS–During the study period 268 defibrillators were purchased by public subscription and 96% of the 2000 ambulance crew underwent an eight hour training programme in cardiopulmonary resuscitation and defibrillation. A total of 1111 cardiac arrests were recorded, and defibrillation was indicated and undertaken in 602 (54%) patients, mean age 63 (range 14-92) years. A spontaneous pulse was present on arrival at hospital in 180 (30%) of the defibrillated patients, and 75 (12.5%) were subsequently discharged alive. As expected, the likelihood of survival was inversely related to the delay from the onset of cardiac arrest to the time of the first shock and was greater in the case of witnessed arrest. If ventricular fibrillation occurred after the arrival of the ambulance, survival to discharge was 33%. CONCLUSIONS–An effective scheme for out of hospital defibrillation can be introduced rapidly, and with limited training implications and costs, by the use of automated external defibrillators in ambulances.